Roles of alloying elements on the corrosion behavior of sputter-deposited amorphous W-Cr-Zr alloys in 0.5m NaCl solution - Bhattarai, Jagadeesh (Scientific World, 2011)
Ternary amorphous W–xCr–yZr alloys containing 9--38 at % tungsten, 15--42 at % chromium and 39--73 at % zirconium were successfully prepared by direct current (DC) magnetron sputtering technique. The corrosion rates of all the examined sputter-deposited W–xCr–yZr alloys were in the range of 1 × 10−3 mm/y or lower which are nearly one order of magnitude lower than those of the sputter-deposited tungsten, chromium and zirconium metals after immersion for 240 h in 0.5 M NaCl solution open to air at 25°C. In particular, the simultaneous additions of tungsten, chromium and zirconium to the amorphous ternary W–xCr–yZr alloys in the chromium- and zirconium-enriched W--91Cr and W--88Zr alloys, respectively, showed a synergistic effects for showing the higher corrosion resistance than those of binary WCr and W--Zr alloys in neutral NaCl solution. Keywords: W–Cr–Zr alloys; Sputter deposition; Corrosion test; Open circuit potential; 0.5 M NaCl DOI: http://dx.doi.org/10.3126/sw.v9i9.5515 SW 2011; 9(9): 34-38